2013
DOI: 10.1039/c3nr00352c
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the nature of plasmon-driven catalytic reactions revealed by HV-TERS

Abstract: The nature of plasmon-driven chemical reactions is experimentally investigated using high vacuum tip-enhanced Raman spectroscopy (HV-TERS). It is revealed that the coupling between the tip and the substrate can produce intense plasmon resonance, which then decays to produce sufficient hot electrons and thus catalyses the chemical reaction. The photoelectron emission from the laser illuminated silver substrate alone cannot drive the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 13 publications
2
58
0
1
Order By: Relevance
“…[74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] Although it has been reported that it is possible to produce azobenzene derivatives from aromatic nitro and amine compounds, the reaction mechanism is not clear. Zhao et al explained the selective formation of azobenzene derivatives from p-substituted nitrobenzenes and anilines using the photoinduced charge transfer model based on TDDFT methods (Figure 9c).…”
Section: Wwwadvopticalmatdementioning
confidence: 95%
See 3 more Smart Citations
“…[74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] Although it has been reported that it is possible to produce azobenzene derivatives from aromatic nitro and amine compounds, the reaction mechanism is not clear. Zhao et al explained the selective formation of azobenzene derivatives from p-substituted nitrobenzenes and anilines using the photoinduced charge transfer model based on TDDFT methods (Figure 9c).…”
Section: Wwwadvopticalmatdementioning
confidence: 95%
“…Based on the mechanistic study performed by HV-TERS, the thermal energy of surface plasmons did not affect the chemical reaction equilibrium, because it is not localized in the nanogap region, being quickly dissipated along the tip and substrate. [81] Moreover, electrical field gradient quadrupole Raman modes were observed in the catalytic reactions of pNTP studied by HV-TERS. [82] For the first time, Sun et al experimentally observed and theoretically interpreted that the electric field gradient contributed to the strong enhancement of Raman and infrared (IR)-active modes of DMAB in HV-TERS spectra, and the simultaneous observation of both modes provided the spectral evidence for ultrasensitive chemical analysis.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, due to the high throughput and low energy requirements, a novel application of plasmonics in chemical reactions gains significant attention, as reported in works on dissociation of hydrogen15, 16 and water,17, 18 photochemical19, 20, 21, 22, 23 and plasmon‐driven chemical reactions,24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37 etc. SPs excited on the surface of gold or silver can non‐radiatively decay into so‐called hot electrons with a high energy between the Fermi and vacuum energy level 36, 37, 38, 39, 40.…”
Section: Introductionmentioning
confidence: 99%